2003
DOI: 10.1208/pt040469
|View full text |Cite
|
Sign up to set email alerts
|

Unilamellar vesicles as potential capreomycin sulfate carriers: Preparation and physicochemical characterization

Abstract: This increasing incidence of TB is attributable to several factors, the most important of which are the HIV epidemic and the lack of control of immigration from countries where TB is common. In fact, untreated HIV infection, leading to progressive immunodeficiency, increases susceptibility to TB, one of the main causes of death in populations with high HIV prevalence. 1-3The aim of this work was to evaluate unilamellar liposomes as new potential capreomycin sulfate (CS) delivery systems for future pulmonary ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…They investigated that DSPC based liposome were found to be within narrow size distribution even less than 200 nm that offered suitability for inhalation formulation. Another authors explored that freeze thaw and surface response methodology was more effective and promising methodology to improve the drug content [53, 54]. Sparfloxacin (Flouroquinolone) was investigated for reduction in growth rate index using liposome loaded sparfloxacin.…”
Section: Current Drug Delivery and Its Limitations In Antimycobacterimentioning
confidence: 99%
“…They investigated that DSPC based liposome were found to be within narrow size distribution even less than 200 nm that offered suitability for inhalation formulation. Another authors explored that freeze thaw and surface response methodology was more effective and promising methodology to improve the drug content [53, 54]. Sparfloxacin (Flouroquinolone) was investigated for reduction in growth rate index using liposome loaded sparfloxacin.…”
Section: Current Drug Delivery and Its Limitations In Antimycobacterimentioning
confidence: 99%
“…In addition, dry powder inhalers (DPIs) are easy to operate and allow the delivery of high doses, which are often required for antibiotics [9]. A few studies have reported the preparation of inhalable powder of capreomycin, some of which were formulated in liposomes or poly(lactic-coglycolic acid) (PLGA) microparticles to control the particles size distribution for efficient lung deposition [10,11]. Hickey et al produced spray-dried powder of capreomycin (as sulfate), in which 50% ethanol (v/v) was used as the solvent and L-leucine as dispersion enhancer [2,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The efficient clearance of exogenous substances from the lungs complicates the successful development of suitable pulmonary anti鈥怲B drug delivery systems. Various approaches to this problem have been reported, such as the use of polymeric microparticles, large porous particles, liposomes and polymeric nanoparticles …”
Section: Introductionmentioning
confidence: 99%